STUDY ON THE APPLICATION OF CASH ACCOUNTING SYSTEM FOR VAT IN ROMANIA - ECOBICI NICOLAE (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2014)
The cash accounting system for VAT has been implemented in Romania as of 1 January 2013 and now turns one year of application in Romania. Since its implementation the system has sparked controversy, being harshly criticised by professional accountants in Romania and elsewhere. Criticisms mainly concerned the following issues: no possibility to choose to apply the system, breach of the VAT neutrality principles, maximum period of 90 days to postpone the chargeability of VAT for unpaid deliveries, while VAT deduction was subject to payment of the value of goods and services invoiced without specifying any term. In this article we would like to examine the extent to which the legislative changes that came into effect as of 1 January 2014 improve the cash accounting system for VAT in Romania. We will also analyse to what extent the system applied in 2013 has brought advantages/disadvantages to the economic entities in Romania based on a survey carried out on a heterogeneous sample of companies in the county of Gorj, regarded as nationally representative. Finally, we intend to compare the cash accounting system for VAT in Romania with its UK counterpart.